Incidence and Predictors of Cannabis-Related Poisoning and Mental and Behavioral Disorders among Patients with Medical Cannabis Authorization: A Cohort Study. (24th August 2022) - Zongo, Arsene; Lee, Cerina; Dyck, Jason R. B.; El-Mourad, Jihane; Hyshka, Elaine; Hanlon, John G.; Eurich, Dean T.
Abstract: Objective: As medical cannabis use increases in North America, establishing its safety profile is a priority. The objective of this study was to assess rates of emergency department (ED) visits and hospitalizations due to poisoning by cannabis, and cannabis-related mental health disorders among medically authorized cannabis patients in Ontario, Canada, between 2014 and 2017. Methods: This is a retrospective cohort study of patients who received medical cannabis authorization in Ontario, Canada, using data collected in participating cannabis clinics. Outcomes included ED visit/hospitalization with a main diagnosis code for: cannabis/cannabinoid poisoning; and mental/behavioral disorders due to cannabis use. Cox proportional hazard regressions were utilized to analyze the data. Results: From 29, 153 patients who received medical authorization, 23, 091 satisfied the inclusion criteria. During a median follow-up of 240 days, 14 patients visited the ED or were hospitalized for cannabis poisoning—with an incidence rate of 8.06 per 10, 000 person-years (95% CI: 4.8–13.6). A total of 26 patients visited the ED or were hospitalized for mental and behavioral disorders due to cannabis use—with an incidence rate of 15.0 per 10, 000 person-years (95% CI: 10.2–22.0). Predictors of cannabis-related mental and behavioral disorders include prior substance use disorders, other mental disorders, age, diabetes, and chronic obstructive pulmonary disease. Conclusions: The results suggest that the incidence of cannabis poisoning or cannabis-related mental and behavioral disorders was low among patients who were authorized to use cannabis for medical care. Identified predictors can help to target patients with potential risk of the studied outcomes.